BOOK REVIEW: CHRISTINE DE PIZAN, “CARTEA CETĂȚII DOAMNELOR” [THE BOOK OF THE CITY OF LADIES], IAȘI, POLIROM, 2015, 745P. - Marian SUCIU (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
Christine de Pizan (1364-1430) is one of the fir st Western women scholars and professional writers. She was the daughter of the Italian physician and astrologer Tommaso di Benvenuto da Pizzano, who moved to Paris to work as the personal adviser to King Charles V, in the middle of the fourteenth century. As the daughter of the king’s adviser, Christine de Pizan had access to the Royal Library at the Louvre. There, under the strict supervision of Gilles Malet, the director of the library, she was raised to become an educated woman. After many beautiful years spent in the Royal Library, at the age of fifteen, she married Étienne, a royal secretary. Unfortunately, her husband died 10 years later, and left her without any financial support. Moreover, she had to stand up to the creditors trying to collect her husband’s debt (sometimes, even more than he owed them). In order to survive as a widow with children, she started to write various types of scholarly texts to earn money. In 1418 she retreated from public life and went to Saint Louis monastery in Poissy, where she spent the rest of her life.